Commuter families: parental readiness, family environment and adolescent school performance - Siaw, Yan Li; Roslan, Samsilah; Abdullah, Maria Chong; Abdullah, Haslinda (Elsevier BV, 2015)
The lifestyle of commuter families contradicts with the traditional families model in Malaysia. Therefore, this study aims to investigate the impact of commuter family on adolescents’ school performance via a simple mediation model. A total of 434 respondents were involved in this study. Results revealed that parental readiness and family environment significantly predicted adolescent school performance. The model accounted 22% of variability in adolescents’ school performance explained by the model (total effect 0.44). Family environment partially mediates the relationship between parental readiness and adolescent school performance. This study highlights the importance of parental readiness to maintain a healthy family development.